Effectiveness of scapular retraction exercises and kinesio taping in individuals with protracted shoulders: A randomized control trial - Divya Gohil; Mokshi Koul; Gaurang Baxi (BLDE University Journal of Health Sciences)
INTRODUCTION: Posture is a position assumed by the body. The protracted shoulder is accompanied by a forward positioning of the head. Kinesiology Taping is a therapeutic tool to unload the fascia and assist in the relief of chronic pain. Retraction exercises reduce the adverse loads on joints and they train the deep postural stabilizing muscles. MATERIALS AND METHODS: After ethical approval, 30 subjects with protracted shoulders in the age group of 18–24 years were selected by simple random sampling, and randomly divided into two groups. Outcome measures assessed were pectoralis minor length and the supine measurement of protracted shoulders. Data were collected four times: pretreatment on day 1, immediate posttreatment on day 1, posttreatment on day 14, and on day 24. RESULTS: Data were analyzed using the PRIMER statistical package software. Repeated Measures ANOVA was used to compare the intragroup differences in measurements for both outcome measures. A T-test was used to compare the intergroup differences. The differences were highly significant (P < 0.05) for all outcome measures, except for pectoralis minor length differences on day 14 and day 24. CONCLUSION: The study concludes that K-Taping has shown higher effectiveness compared to retraction exercises in protracted shoulders.